Pragmatic guide to Subversion - Mason, Mike, 1977- (Pragmatic programmers., 2010)
Subversion is the most popular open-source version control system on the planet. Development teams-big and small, enterprise and open source-use this fast, feature-rich tool daily. Pragmatic Guide to Subversion presents the 48 essential tasks you need to know. It's your shortcut to the Subversion master's recommended set of best practices. With this book, you can get to the good parts quickly, and be more productive and effective.